2009
DOI: 10.1007/s10311-009-0265-3
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary assessment of levels of antifouling booster biocides in harbours and marinas of the island of Gran Canaria, using SPE-HPLC

Abstract: An analytical procedure was developed to allow for the study of the levels of concentration of biocides in the various different ports on the island of Gran Canaria, The Canary Islands. The analytes studied were extracted from water samples using solid-phase extraction and then determined by high-performance liquid chromatography using a diode array detector. The relative standard deviations of the developed procedure were under 12%. Recoveries over 85% and limits of detection between 0.007 and 0.4 lg/L were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The pretreatment method was modified from previous studies by Gonzalez-Toledo et al, 2002;Vidal et al, 2003;Zachariadis and Rosenberg, 2009;Rodríguez et al, 2011. Marine sediment samples (10 g) were extracted by mechanical shaking (15°C, 150 rpm, 1 h), following by sonication (15 min) with 60 mL hexane. Atrazine-d5 and TPT-d15 were spiked as internal standards before the extraction.…”
Section: Pretreatment and Instrumental Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The pretreatment method was modified from previous studies by Gonzalez-Toledo et al, 2002;Vidal et al, 2003;Zachariadis and Rosenberg, 2009;Rodríguez et al, 2011. Marine sediment samples (10 g) were extracted by mechanical shaking (15°C, 150 rpm, 1 h), following by sonication (15 min) with 60 mL hexane. Atrazine-d5 and TPT-d15 were spiked as internal standards before the extraction.…”
Section: Pretreatment and Instrumental Analysismentioning
confidence: 99%
“…The experimental method applied in this study was based on a previously reported from the method test study (Gonzalez-Toledo et al, 2002;Vidal et al, 2003;Zachariadis and Rosenberg, 2009;Rodríguez et al, 2011). We performed the method test that 3 of same sediment samples were spiked with known concentrations of target analytes and went through the modified experimental method to confirm the accuracy and precision.…”
Section: Qa/qcmentioning
confidence: 99%